Effect of stress dependent creep ductility on creep crack growth behaviour of steels for wide range of C*. (April 2015) - Zhang, J. W.; Wang, G. Z.; Xuan, F. Z.; Tu, S. T.
Abstract : In this work, the effect of stress dependent creep ductility on the creep crack growth (CCG) behaviour of steels has been investigated by finite element simulations based on ductility exhaustion damage model. The relationship between the transition region of creep ductility and the transition behaviour of CCG rate on d a /d t - C * curves has been examined and the CCG life assessments of components and CCG resistance of materials for a wide range of C* were discussed. The results show that with increasing the transition region size of creep ductility, the transition C* region size on d a /d t - C * curves increases. With moving transition region position of creep ductility to high stress region (increasing transition stress levels), the transition C* region on the d a /d t - C * curves also moves to high C* region. Decreasing transition stress levels and transition region sizes of creep ductility and increasing the lower shelf and upper shelf creep ductility values can improve the CCG resistance of materials. If the extrapolation CCG rate data from the high C* region or from the transition C* region are used in life assessments of the components at low C* region, the non-conservative or excessive conservative results may be produced. Therefore, the CCG rate data should be obtained for a wide range of C* by long term laboratory tests or numerical predictions using the stress dependent creep ductility and model.